COST AND TIME PERFORMANCE ANALYSIS ON CONTROLLING CONTRUCTION PROJECTS WITH “PERT” METHOD - Achmad Safri Syamsudin; Julistyana Tistogondo; Diah Ayu Restuti Wulandari (NAROTAMA UNIVERSITY, Indonesia, 2023)
In the matter of parking lot problems, there are many ways to solve the problems that always arise from the parking lot with more and more and require a very large land with adequate capacity, therefore one of them is by making a multi-storey parking building. The more development of construction work, the more problems that arise during construction, one of which is project management problems which before the implementation or implementation of development are always planned to determine the schedule, time, and cost needed. In the construction of the Airlangga University multi-storey parking building project, controlling the schedule of the plan should have been carried out in 300 days. With the CPM and PERT methods used, the calculation duration is 340 days with a probability of 99.85% to speed up work and delays. Acceleration is carried out by adding workers so that it will affect costs, so after adding workers with normal costs of Rp. 49.139.000.850,26. and after the addition of manpower to speed up the implementation time with a total cost of Rp 49,227,563,678.83. after accelerating.